ANTIHYPERGLYCEMIC AND LIPID LOWERING ACTIVITIES OF ETHANOLIC EXTRACT OF ERIOBOTRYA JAPONICA SEEDS IN ALLOXAN INDUCED DIABETIC RATS - Shafi, Sabeeha; Tabassum, Nahida (European Scientific Journal, ESJ, 2013)
Diabetes is a metabolic disorder characterized by hyperglycemia, hypertriglyceridemia and hypercholesterolemia, resulting from defects in insulin secretion or action or both. India is known as the diabetic capital of the world. The study of plants having antihyperglycemic and hypolipidemic activities gives a new approach in the treatment of diabetes mellitus. The study was carried out to evaluate the antidiabetic and hypolipidemic activity of ethanolic extract of seeds of Eriobotrya japonica (EBJS) in alloxan induced diabetic albino rats. Diabetes was induced in albino rats by administration of alloxan monohydrate (120 mg/kg) by intraperitoneal route. Rats were divided into 6 groups of 6 animals each. Group I served as non-diabetic control, Group II as diabetic control, Group IIIrd received antidiabetic standard drug (10 mg/kg of glibenclamide) Group IV and Group V received 100 and 200 mg/kg b.w of EBJS. Blood samples were analysed for blood glucose on day 1,4,7 and day 10 th and lipid profile was analysed on day 10. All the values are expressed as Mean+SEM. The results were subjected to statistical analysis using one-way ANOVA followed by students t test. p<0.001 was considered highly significant. The ethanolic extract of EBJS at the dose of 200 mg/kg body weight showed highly significant reduction in blood glucose and serum lipid profile levels in alloxan induced diabetic rats. It is concluded that ethanolic extract of EBJS is effective in controlling blood glucose levels and in improving lipid profile in diabetic rats.